History lessons : teaching, learning, and testing in U.S. high school classrooms - Grant, S. G. (L. Erlbaum, 2003)
In this book, extended case studies of two veteran teachers and their students are combined with the extant research literature to explore current issues of teaching, learning, and testing U.S. history. It is among the first to examine these issues togeth.